EFFICACY OF DISINFECTANTS AGAINST GRAM-POSITIVE BACTERIA FOUND ON THERMOPLASTIC RETAINERS - ISMAH, NADA; PURWANEGARA, MIESJE K.; RAHMAWATI, TUTI (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study aimed to compare the efficacy of two disinfectants against Gram-positive bacteria, particularly Streptococcus mutans, for use as a disinfectant for dental retainers. Methods: In total, 35 thermoplastic retainers in this study were categorized into three immersion groups: control group; mouthwash group, using chlorhexidine 0.1%; and denture cleanser tablet group. The retainers were worn for 15 days, and Gram-positive bacteria were enumerated before and after the retainers were immersed. Results: We found a significant difference in bacterial numbers between the two disinfectant groups and the non-disinfectant or control group. Both disinfectant groups had decreased numbers of Gram-positive bacteria. Conclusions: Disinfectant use is effective in decreasing the load of Gram-positive bacteria on thermoplastic retainers.